ETIKA POLITIK PAUL RICOEUR - David Rabim (Program Studi Filsafat Universitas Katolik Widya Mandira Kupang, 2023)
The focus of this paper is Paul Ricour's philosophy of political ethics; addressing the phenomenon of injustice towards others in practical politics in Indonesia. The author reviews it using a text analysis method based on the book Oneself as Another. In the book, Ricoeur defines political ethics as